Order, displacements and recurring financial crises - Andreas Hoffmann; Björn Urbansky (Universität Leipzig, Wirtschaftswissenschaftliche Fakultät, 2012)
The paper describes boom-and-bust cycles within Hayek's framework of order and aims to provide an understanding of recurring crises in recent financial history. We argue that a boom-and-bust cycle is initiated by a displacement that lowers the degree of (ex-post) plan coherence (or order) in an economy. Such displacements can be endogenous (e.g. innovations) or exogenous (e.g. policy alteration). A cycle can be triggered if the displacement signals high short-run profit opportunities but agents lack an understanding of the long-run impact of the displacement and cannot form coherent expectations. The application of the framework aims at making sense of recurring financial crises since the break-down of the Bretton Woods System. First, we argue that the newly emerging international financial architecture has made the financial system more elastic. Second, we show how large exogenous displacements such as capital account liberalization inititated boom-and-bust cycles in developing countries. And third, we argue that the competitive market system themselves brought about many innovations that endogenously amplified the latest US boom-and-bust cycle and increased the crisis potential.
Keywords: E32; B5; 330; Hayek; order; displacement; financial crises; Finanzmarktkrise; Konjunktur; Wirtschaftsordnung; Marktmechanismus; Evolutionsökonomik; Theorie